2011
DOI: 10.1136/thoraxjnl-2011-201054c.259
|View full text |Cite
|
Sign up to set email alerts
|

P259 Effects of metformin on clinical outcome in patients hospitalised for COPD exacerbations: a retrospective cohort study

Abstract: Conclusion In acute exacerbation of COPD there is no difference between 7-day and 14-day courses of treatment with oral prednisolone. The peak of FEV 1 and FVC in 7-day group on day-10 where corticosteroid was already stopped on day-7, (peak in 14-day group was on day-7) might be due to some other factor/factors responsible which would be cleared by further study. Clinical implications There was no difference between 7-day and 14-day courses of prednisolone treatment, so, 7-day might be the shortest effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As Kim et al (20) expanded the OHA according to our selection criteria, we eventually excluded their report from this study. Finally, six articles (involving 3,467 participants) were included in our review: one was an RCT (15), four were retrospective studies (13,(21)(22)(23) (three were published as abstracts) and the last ( 14) was…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Kim et al (20) expanded the OHA according to our selection criteria, we eventually excluded their report from this study. Finally, six articles (involving 3,467 participants) were included in our review: one was an RCT (15), four were retrospective studies (13,(21)(22)(23) (three were published as abstracts) and the last ( 14) was…”
Section: Resultsmentioning
confidence: 99%
“…Four articles (13,15,21,23) Lactic acidosis, defined as a lactate concentration of ≥5 mmol/L was not reported. All of the above indicated that there were no significant differences between the two groups.…”
Section: Lactate Concentrationmentioning
confidence: 99%